Clinical features of the Abrikossoff intraocular granular cell tumor development - M. A. Golovanova; A. N. Denisenko; E. V. Tsyganova (Российский офтальмологический журнал, 2020)
The etiology of Abrikossoff granular cell tumor remains uncertain. No clinical data on the growth of the intraocular granular cell tumor could be found in Russian literature available to the authors.Purpose: to describe the growth and particularities of the Abrikossoff tumor and to offer plausible ideas concerning its etiology.Material and methods. For a year, we observed a clinical case of the growing tumor in a female patient who had refused to have her eyeball enucleated.  Every 3 months the patient was subjected to biomicroscopic examination, В-scan, and optical coherence tomography.Results. After the hemophthalmus treatment,  the patient revealed a dark brown neoplasm with a slight prominence from the optic disk to the macular area with no distinct boundaries. A year later, enucleation was performed and, an intraocular granular Abrikosoff cell tumor was diagnosed by the results of an immunohistochemical test. A low expression of vimentin was detected, accompanied  by a strong and stable S-100 expression. Melan A, OLA or Ki-67  were not expressed.Conclusion. Since the tumor does not respond to chemotherapy or radiation therapy, the only treatment method is enucleation or complete removal in case of any other localization.